CAPITAL STRUCTURE AND FINANCIAL PERFORMANCE OF LISTED INFORMATION AND COMMUNICATIONS TECHNOLOGY FIRMS IN NIGERIA - Nasiru Adamu Kanoma; Nurudeen Usman Miko; Augustine Ayuba; Idris Mohammed; Idris Mohammed; Mark G Tagwai (Gusau Journal of Accounting and Finance)
This study seeks to examine the effect of capital structure on financial performance of the listed information and communications technology firms in Nigeria. This study adopted correlation and ex-post facto research design. The population of this study consists of all listed information and communications technology firms in Nigeria. Census sampling technique was employed. Multiple regression model based on pooled ordinary lease square, robust test was adopted in analyzing the panel data obtained from audited financial statement of the listed sampled information and communications technology firms for the periods of 10 years between (2013- 2022). The study reveals that both long term debt financing ratio short term debt financing, and debt to equity financing ratio have positive and significant influence on return on assets of the listed information and communications technology firms in Nigeria. On the other hand, equity financing ratio has a positive but insignificant effect on performance of listed information and communications technology companies in Nigeria. Therefore, it is recommended that the management of the listed information and communications technology firms in Nigeria should initiate coherent and integrated financial policies towards encouraging long-and short-term debt financing and debt to equity financing to ultimately improve the financial performance of the list information and communications technology firms in Nigeria.